The neurobiology of social play and its rewarding value in rats. (November 2016) - Vanderschuren, Louk J.M.J.; Achterberg, E.J. Marijke; Trezza, Viviana
Highlights: Social play behaviour is a highly rewarding social activity abundant in young animals. Social play behaviour facilitates the development of brain and behaviour. The rewarding properties of social play can be studied using pertinent paradigms. Social play behaviour is mediated by a distributed network of corticolimbic structures. Opioids, dopamine and endocannabinoids interact in the modulation of social play. Abstract: In the young of many mammalian species, including humans, a vigorous and highly rewarding social activity is abundantly expressed, known as social play behaviour. Social play is thought to be important for the development of social, cognitive and emotional processes and their neural underpinnings, and it is disrupted in pediatric psychiatric disorders. Here, we summarize recent progress in our understanding of the brain mechanisms of social play behaviour, with a focus on its rewarding properties. Opioid, endocannabinoid, dopamine and noradrenaline systems play a prominent role in the modulation of social play. Of these, dopamine is particularly important for the motivational properties of social play. The nucleus accumbens has been identified as a key site for opioid and dopamine modulation of social play. Endocannabinoid influences on social play rely on the basolateral amygdala, whereas noradrenaline modulates social play through the basolateral amygdala, habenula and prefrontal cortex. In sum, social play behaviour is the result of coordinated activity in a network of corticolimbic structures, and its monoamine, opioid and endocannabinoid innervation.